Core stability training on lower limb balance strength - Dello Lacono, A.; Padulo, J.; Ayalon, M. (Journal of Sports Sciences, 2016)
This study aimed to assess the effects of core stability training on lower limbs` muscular asymmetries and imbalances in team sport. Twenty footballers were divided into two groups, either core stability or control group. Before each daily practice, core stability group (n = 10) performed a core stability training programme, while control group (n = 10) did a standard warm-up. The effects of the core stability training programme were assessed by performing isokinetic tests and single-leg countermovement jumps. Significant improvement was found for knee extensors peak torque at 3.14 rad/s (14%; P < 0.05), knee flexors peak torque at 1.05 and 3.14 rad/s (19% and 22% with P < 0.01 and P < 0.01, respectively) and peak torque flexors/extensors ratios at 1.05 and 3.14 rad/s (7.7% and 8.5% with P < 0.05 and P < 0.05, respectively) only in the core stability group. The jump tests showed a significant reduction in the strength asymmetries in core stability group (-71.4%; P = 0.02) while a concurrent increase was seen in the control group (33.3%; P < 0.05). This study provides practical evidence in combining core exercises for optimal lower limbs strength balance development in young soccer players.